Botulinum Toxin in Management of Benign Essential Blepharospasm - Afzal, Farzana; Robi, Nazmul Haque; Sultana, Sadia; Rashid, Riffat; Habib, Nasrin; Rashid, Mamunur (Journal of Ophthalmology and Research, 2021)
The objective of this study is to evaluate effectiveness of botulinum toxin injection in treatment of benign essential blepharospasm. It is a prospective interventional study conducted in Ispahani Islamia Eye Institute and Hospital within the period of June 2018 to May 2020. In this study 102 patients, suffering from benign essential blepharospasm, were included. After taking standard precaution, botulinum toxin injection was injected at 5 to 6 sites of each eye with 2.5 units per site. Patients were followed up routinely on the following day, after 7 day, then after 1 month and 3 months. 65.68% patients are of 50 years or more with mean age 54.91 years. 35.29% patients are male and 64.70% are female. 62.74% patient had bilateral blepharospasm while 37.25% patient presented with unilateral symptoms. Useful effect of injection appeared within 48 hours in all patients. According to Blepharospasm disability index, 13.72% patient had minor blepharospasm (mean BSDI score 1to 2), 34.31% patient had moderate (mean BSDI score >2 to 3) and 51.96% patient had severe blepharospasm (>3 to 4). Baseline mean BSDI score before injection of 102 patients was 2.62. 7 days after injection, the score reduced to 1.46 and after 1month, score was 0.95. Minor transient side effect like ptosis, dry eye and lagophthalmos was found in very few patients. The useful effect of injection lasted for 3-4 months in majority of patients. This study explored Botulinum toxin as the first line treatment of benign essential blepharospasm,however, there are few limitations of this agent, including short-term effect, repeated application, and high cost.